A review of the taxonomy and phylogenetics of the curvicauda species group within the genus Anastrepha in Mexico including descriptions of new taxa - Hernández-Ortiz, Vicente; Fuente, Laura Navarro De La; Covarrubias, Rodrigo Lasa (Zootaxa, 2025)
We present a taxonomic study of Mexican fruit fly populations previously identified as Anastrepha curvicauda (Gerstaecker), describing two new taxa from Mexico, A. magnifica, new species, and A. curvicauda flavigaster, new subspecies. In addition, the phylogenetic relationships between the population samples are analysed using mitochondrial sequences of the COI gene. The results provide new insights into the geographical distribution and natural history of the Mexican species.